Outside the Band : Depreciation and Inflation Dynamics in Chile - Perez Ruiz, Esther (IMF Working Papers; Working Paper ;, 2016)
This paper examines inflation dynamics in Chile during the last peso depreciation episode 2013-15. The evidence is for substantial pass-through effects to inflation, given the large and persistent depreciation movement. Widespread indexation practices in non-traded goods markets are found to amplify the inflation response to the depreciation, while the role of wage indexation is less relevant to the inflation dynamics. Overall, inflation would have remained within the central bank's target band absent the peso depreciation. The analysis also shows that tightening monetary policy in response to a depreciation shock can be costly in terms of output: the response of activity to rates is found to be strong, while the transmission from activity to inflation is found to be weak. Simulations under uncertainty about the extent of the pass-through also suggest that monetary policy can play a countercyclical role in the face of depreciation shocks at a moderate inflationary cost, as long as inflation expectations remain anchored.